Endovascular Treatment of Abdominal Aorta Floating Thrombus in a Patient with Recurrent Peripheral Embolization and COVID-19. (April 2023) - Giannetta, Matteo; Mazzaccaro, Daniela; Righini, Paolo; Nano, Giovanni
Purpose: To present stent-graft treatment of floating thrombus in the abdominal aorta. A review of the literature about aortic floating thrombus (AFT) was also performed. Case report: A 56-year-old female with no risk factors for vascular disease but with history of a mild COVID-19 infection in the previous month, for which she had started anticoagulant therapy at a prophylactic dosage, developed an acute ischemia of the lower limbs and was diagnosed with floating thrombosis of the abdominal aorta. The thrombus was excluded from the aortic blood flow by deployment of a stent-graft in the abdominal aorta. At 12 months, the patient was well, and the thrombus in the abdominal aorta appears to be completely excluded by the stent-graft. A review of the available literature from 1980 to 2022 showed 74 cases of AFT located in the aortic arch, in the descending thoracic and in the abdominal aorta. In most cases the AFT involved the aortic arch (38/74, 51.3%) and/or the descending thoracic aorta (30/74, 40.5%), while the abdominal aorta was involved in 6 cases. In 2 of these 6 cases, the patients had a COVID-19 infection. The AFT was mostly approached either medically with anticoagulation/systemic thrombolysis (32/74, 43.2%) or with surgical removal (31/74, 41.9%), while endovascular coverage of the thrombus with an endograft was performed in 6 cases of AFT located in the aortic arch and in the descending thoracic aorta (3 cases each). Conclusion: There is no consensus about the optimal treatment of AFT. In selected cases, abdominal stent-grafts may be used for stabilization and exclusion of symptomatic abdominal aorta floating thrombosis to prevent progression and recurrent embolization.